Immunotherapy strategies targeting tumor-associated macrophages and their mechanisms of action in tumor progression - Zhu, Haixia; Shao, Jingjing; Shao, Lili; Cai, Liuhuan; Gu, Chunyan; Ge, Qin; Liu, Jibin (Frontiers in Immunology, 2025)
The tumor microenvironment significantly influences the aggressive invasive characteristics of human solid tumors, with the infiltration of immune cells being a defining feature of tumor advancement. Among the diverse cell types present in the tumor microenvironment, tumor-associated macrophages (TAMs) stand out as crucial regulatory centers in the interplay between tumors and the immune system. Recent developments in single-cell sequencing technologies, combined with an expanding body of research, have revealed the functional diversity and heterogeneity of TAMs, as well as the mechanisms through which they interact within the tumor microenvironment. This indicates that TAMs could represent innovative targets for therapies aimed at tumors, thus promoting the creation of tailored anti-cancer strategies. This article provides a review of the various types of TAMs, their influence on tumor development and progression, their regulatory functions in tumor activities, and the progress in tumor immunotherapy that focuses on targeting TAMs.